Abnormal behaviours during pramipexole treatment for Cotard's syndrome: a case report. Issue 4 (29th September 2015) - Maruo, Joji; Haraguchi, Yoshinori; Tateishi, Hiroshi; Noguchi, Tomoyuki; Mizoguchi, Yoshito; Kato, Takahiro A.; Kawashima, Toshiro; Monji, Akira
Abstract: Cotard's syndrome is a relatively rare condition that involves a delusion of negation in which an individual believes he or she has lost his or her soul, is dead, or is without functional body systems. This syndrome is observed in various neuropsychiatric disorders but most commonly in mood disorders. Pramipexole has often been used in the adjunctive treatment of both bipolar and unipolar depression, and it is known to cause rare but serious adverse effects such as compulsive behaviours in the treatment of Parkinson's disease. Here we report a case of Cotard's syndrome in treatment‐resistant major depression associated with abnormal behaviours that might be caused by pramipexole. In the present case, the patient's abnormal behaviours gradually disappeared about 2 months after the discontinuation of pramipexole. The hypoperfusion in the bilateral parieto‐occipital lobe found on single‐photon emission computed tomography suggests the presence of Lewy body disease pathology. Nonetheless, the patient's abnormal behaviours disappeared after the discontinuation of pramipexole, indicating that they are mainly attributable to pramipexole treatment. However, the possible existence of Lewy body pathology could facilitate the emergence of abnormal behaviours after treatment with pramipexole. The patient's abnormal behaviours, such as eating other patients' food and taking her medicine before the scheduled time, might differ from typical compulsive behaviours induced by pramipexole (such as pathological gambling and hypersexuality), but they could be regarded as disinhibition. Therefore, we should follow up on the clinical course of this case carefully through neuroimaging investigation and neurocognitive assessment.